Compromising situation of India's bio-medical waste incineration units during pandemic outbreak of COVID-19: Associated environmental-health impacts and mitigation measures. (1st May 2021) - Thind, Parteek Singh; Sareen, Arjun; Singh, Dapinder Deep; Singh, Sandeep; John, Siby
Abstract: COVID-19 induced pandemic situations have put the bio-medical waste (BMW) management system, of the world, to test. Sudden influx, of COVID-infected patients, in health-care facilities, has increased the generation of yellow category BMW (Y-BMW) and put substantial burden on the BMW-incineration units of India. This study presents the compromising situation of the BMW-incineration units of India, in the wake of COVID-19 pandemic, from 21st March 2020 to 31st August 2020. This analysis revealed that on an average each COVID-infected patient in India generates approximately 3.41 kg/d of BMW and average proportion of Y-BMW in it is 50.44%. Further, it was observed that on 13th July 2020, the total Y-BMW, generated by both the normal and COVID-infected patients, fully utilized the BMW-incineration capacity of India. Also, it was made evident that, during the study period, BMW-incineration emitted several pollutants and their concentration was in the order: NOx  > CO > SOx  > PM > HCl > Cd > Pb > Hg > PCBs > Ni > Cr > Be > As. Subsequently, life time cancer risk assessment depicted that with hazard quotient >10 −6, Cd may induce carcinogenic health impacts on both the adults and children of India. Therefore, to mitigate the environmental-health impacts associated with the incineration of BMW, evaluation of various options, viz., alternative technologies, substitution of raw materials and separate treatment of specific wastes, was also done. It is expected that the findings of this study may encourage the global auditory comprising scientific community and authorities to adopt alternate BMW-management strategies during the pandemic. Graphical abstract: Image 1 Highlights: COVID-induced BMW generation in India is 3.41 kg/d/patient. India's incineration capacity was compromised by 13th July 2020 during the pandemic. Incineration of COVID-BMW emitted metals in the order: Cd > Pb > Hg > Ni > Cr > Be > As. Life time cancer risk associated with Cd-emissions was observed to be > 10 −6 Alternate technologies and waste-specific treatment can reduce emissions. Abstract : Generation of yellow-BMW in India, during pandemic, was estimated to assess the compromising capacity of its incineration units and associated environmental-human health impacts.